Tariff Jumping Foreign Investment and Capital Taxation - Vivek Dehejia; Alfons Weichenrieder (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper reconsiders the welfare effects of tariff jumping direct investment if mobile capital is subjected to taxation. In contrast to the conventional wisdom, the receiving country may in this case gain from the incremental inflow of capital, as this diverts tax revenues from the rest of the world. In the case of perfect capital mobility, this possibility becomes a certainty. Our argument provides one rationale for a small country to levy a distorting tariff in a second best world in which capital taxes already exist.
Keywords: 330; Capital taxation; tariff jumping; foreign direct investment